Clinical and Surgical Insights into Primary CNS Lymphoma in Immunocompetent Patients - Mahantshetti, Prakash; Parajiya, Ram; Kalyanshetti, Nikhita; Modi, Mehul; Prem D, Prem D (Journal of Neonatal Surgery, 2025)
Primary Central Nervous System Lymphoma (PCNSL) is a rare and aggressive extranodal non-Hodgkin lymphoma confined to the brain, eyes, and cerebrospinal fluid, with an incidence of 0.47 per 100,000 person-years. It accounts for 4%–6% of extranodal lymphomas and 4% of newly diagnosed CNS tumors. While commonly associated with immunocompromised states such as AIDS and organ transplantation, PCNSL in immunocompetent patients remains rare. The majority of cases are diffuse large B-cell lymphomas (DLBCLs), with other subtypes being extremely uncommon. This case series presents five immunocompetent patients diagnosed with PCNSL at different intracranial locations, including atypical presentations in the cerebellum and cranial bones. Clinical symptoms ranged from focal neurological deficits, behavioral changes, and symptoms of increased intracranial pressure to localized swelling. Imaging revealed homogenously enhancing lesions, often in the supratentorial region, consistent with prior literature. All patients underwent surgical resection, primarily for diagnostic confirmation and decompression, followed by referral for oncological management. Histopathology confirmed high-grade B-cell lymphoma in all cases. Our findings emphasize the variability in clinical and radiological presentations of PCNSL, necessitating a high index of suspicion for timely diagnosis. While the definitive treatment remains unclear, high-dose methotrexate combined with whole-brain irradiation is considered effective, and surgical resection can improve outcomes in select cases. This series highlights the need for multidisciplinary approaches to optimize management and improve prognosis in this challenging disease.